Laser Refractography - Rinkevichyus, B.S.; Evtikhieva, O.A.; Raskovskaya, I.L.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
This book describes the basic principles of laser refractography, a flexible new diagnostic tool for measuring optically inhomogeneous media and flows. Laser refractography is based on digital imaging and computer processing of structured laser beam refraction (SLR) in inhomogeneous transparent media. Laser refractograms provide both qualitative and quantitative measurements and can be used for the study of fast and transient processes. In this book, the theoretical basis of refractography is explored in some detail, and experimental setups are described for measurement of transparent media using either 2D (passed radiation) or 3D (scattered radiation) refractograms. Specific examples and applications are discussed, including visualization of the boundary layer near a hot or cold metallic ball in water, and observation of edge effects and microlayers in liquids and gases. As the first book to describe this new and exciting technique, this monograph has broad cross-disciplinary appeal and will be of interest to students and researchers who need to characterize complex fluid behavior.
Structured Laser Radiation (SLR) -- Physical Processes Giving Rise to Optical Inhomogeneities in Media -- Refraction of Laser Beams in Layered Inhomogeneous Media -- Refraction of Structured Laser Radiation in Spherical Temperature Inhomogeneities -- Laser Refractographic Systems -- Digital Refractogram Recording and Processing -- Laser Refractography$1 (Ba Method for Quantitative Visualization of Optically Inhomogeneous Media.s
Keywords: Physics; Computer vision; Hydraulic engineering; Physics; Laser Technology, Photonics; Engineering Fluid Dynamics; Image Processing and Computer Vision; Fluid- and Aerodynamics; Signal, Image and Speech Processing